Penerapan Pembelajaran Guided Discovery Learning dengan Laboratorium Virtual terhadap Keterampilan Proses Sains Siswa - Seftriana, Sofia Mega; Hadi, Wiwin Puspita; Wulandari, Ana Yuniasti Retno; Rosidi, Irsad; Yasir, Mochammad (Universitas PGRI Semarang, 2023)
The low level of science process skills, lack of variety of learning models, and limited laboratory facilities are the problems that underlie this research. This research uses quantitative research with the pre-experimental method with one group pretest-posttest research design. The sampling technique used was a non-probability sampling technique with a purposive sampling type with the sample used in this study was 32 students of class VIII C UPT SMP Negeri 22 Gresik in the 2021-2022 academic year. Data collection techniques through science process skills tests, student response questionnaires, and observation of learning implementation. The result showed that: 1) the paired sample t-test analysis obtained a significance of 0.000 0.05 and t count -t table with (-64,266 -2,0395), indicating that there were differences in students' science process skills before and after the application of the guided discovery learning model with a virtual laboratory on students' science process skills. 2) The test of students' science process skills after the application of the guided discovery learning model with a virtual laboratory was 71% in the high category. Based on these results, it can be conclution that there are differences in students' science process skills before and after the application of guided discovery learning with virtual laboratories.